2020
DOI: 10.1016/j.ebiom.2020.102804
|View full text |Cite
|
Sign up to set email alerts
|

DRH1 – a novel blood-based HPV tumour marker

Abstract: Background: To date, no studies have successfully shown that a highly specific, blood-based tumour marker to detect clinically relevant HPV-induced disease could be used for screening, monitoring therapy response or early detection of recurrence. This study aims to assess the clinical performance of a newly developed HPV16-L1 DRH1 epitope-specific serological assay. Methods: In a multi-centre study sera of 1486 patients (301 Head and Neck Squamous Cell Carcinoma (HNSCC) patients, 12 HIV+ anal cancer patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
(22 reference statements)
1
9
0
Order By: Relevance
“…We value all comments on our research, and the opportunity to provide further information on our study describing the HPV16-specific tumour marker DRH1 [1] .…”
mentioning
confidence: 99%
“…We value all comments on our research, and the opportunity to provide further information on our study describing the HPV16-specific tumour marker DRH1 [1] .…”
mentioning
confidence: 99%
“…Recently, HPV16‐L1 DRH1 epitope‐specific serum Abs, rather than lifetime exposure to HPV, were linked to HPV16‐induced malignant disease. Serum DRH1 Abs showed a 95% sensitivity for HPV16‐driven OPSCC, and the diagnostic specificity was 99.46% for men and 95.6% for women 26 . However, this test was limited to patients with HPV‐related HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Serum DRH1 Abs showed a 95% sensitivity for HPV16‐driven OPSCC, and the diagnostic specificity was 99.46% for men and 95.6% for women. 26 However, this test was limited to patients with HPV‐related HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that HPV16 E6 antibodies may have potential clinical utility for the diagnosis and/or prognosis of HPV-driven OPSCC. However, Weiland and co-workers [ 60 ] published only recently a study utilizing a novel HPV16-L1 DRH1 epitope-specific antibody applied in a multi-center study analyzing sera from 1486 patients suffering from various HPV-associated diseases. Here, the authors showed a decline in post-treatment antibody levels and concluded that HPV16-L1 DRH1 epitope-specific antibodies are linked to HPV16-induced cancer.…”
Section: Detection Methodsmentioning
confidence: 99%